Technical and tactical aspects in Italian youth rugby union in relation to different academies, regional tournaments, and outcomes - Ungureanu, A. N.; Condello, G.; Pistore, S.; Conte, D.; Lupo, C. (The Journal of Strength and Conditioning Research, 2019)
This study aimed to analyze the technical and tactical aspects of the Italian under-18 Academy Rugby Union in relation to different academies, regional tournaments, and game outcomes. A notational analysis (44 indicators) was performed on 16 games (2014-15 season) to evaluate strong differences (p = 0.05; moderate-large effect sizes [ESs]) according to variables. Among academies, strong differences were showed for defensive breakdown, in which the defending support is much (range = 77-87%), equal (range = 11-32%), and less (range = 2-12%) numerous than the attacking support, total tackles (range = 64-122), and passes (range = 72-151), pass to possession ratio (range = 6-10), possession lost due to an error (range = 28-59%), and ball in play in own (range = 8-25%) and opponent (range = 7-31%) 22-m area indicators. For tournaments, effects emerged for offensive breakdown when the ball is used quickly using maximum 2 attacking supports (range = 20-30%) and is not used quickly (range = 28-41%), total penalty kicks (range = 11-16), and sequences period 0-10 (range = 26-35%) and 10-40 seconds (range = 47-55%). Conversely, winning and losing academies reported differences with small ESs. These results highlight that the technical and tactical aspects of the Italian under-18 Academy Rugby Union are quite homogeneous, suggesting that FIR coaching staffs are more oriented to players' skills than successful games. However, tactical and strength and conditioning coaches can benefit from the findings of this study, focusing training on cognitive, strength, and repeated sprint abilities with and without change of direction for improving the occurrence of "set pieces won/regained" and "ball in play in opponent 22 m area," which appear as the key of the game in this rugby competition level.